Political pressure on the National Bank of Slovakia - Peter Kukuk; Adam Geršl (Charles University in Prague, Institute of Economic Studies (IES), 2011)
This paper analyzes political pressure on the National Bank of Slovakia, using the Havrilesky (1993) methodology based on media signalling. This methodology allows the pressure on the Central Bank of Slovakia to be compared with the pressure on the central banks to which the methodology was already applied, namely - the U.S. Federal Reserve, the Deutsche Bundesbank and the Czech National Bank. The analysis and the comparison reveals a relatively weak signalling of pressure in media in Slovakia and prevailance of financial sector representatives as the main commentaries on monetary policy of the National Bank of Slovakia in the period before euro adoption.
Keywords: E52; D78; 330; political economy; central banks; monetary policy